(untitled) (Intercom - Brazilian Journal of Communication Sciences, 2023)
This study aims to understand the interfaces between communication and (im)material consumption regarding the event Arrastão do Pavulagem, in the city of Belém, in the context of the Covid-19 pandemic. It was used the intersection of netnographic analysis, interviews with semi-structured script and snowball sampling. It was possible to observe that the subjects seek to relate to objects that trigger, with greater frequency, in their subjectivities, sensations of belonging to a particular social group through contact with the local culture. Such objects trigger memories of past experiences that marked collective and subjective experiences and that, when configured as materializations of popular cultures of the state of Pará and neighboring states, are present in the events held by the Instituto Arraial do Pavulagem.